Design of Real-time Processing Function of High-speed Maglev Train Signal System - FAN Liang; FANG Kai; YIN Yuan (Kongzhi Yu Xinxi Jishu)
High-speed maglev train control puts forward higher requirements on the response time of signal system. As the response time of signal system increases, the event processing time will be shortened, some events cannot be processed in real time, and the existing signal system cannot solve this problem well. In order to solve the problem that all events can be handled in real time under unfavorable conditions, this paper proposes a real-time processing modeling method, which analyzes the load capacity in a cycle through a rate monotone method, and adopts a clock driven task scheduling algorithm to avoid the impact of multi-event synchronous triggering on the system. Real-time performance of the signal system is analyzed through modeling, and then the relevant parameters and performance indicators are determined. This can reduce the timeout error caused by unreasonable time-sharing of events and avoid bringing the problem into the later design stage.